Estudo e aplicações das técnicas de RMN HR-MAS e DOSY em plantas e extratos de plantas da ordem Rutales - Vizzotto, Lucinéia (Universidade Federal de São Carlos, 2004)
This work describes the implementation of two recent techniques in NMR - DOSY e HR-MAS as a tool for the analysis of natural products mixture and in leaves of Citrus, respectively. The work begun with the technique DOSY, in which a known mixture of two natural products was employed to implement the technique and optimise the experiments of DOSY, DOSY-COSY and DOSY-HSQC. After that, the DOSY experiments was employed in a group of natural products mixtures, in which the technique applicability was assessed. The second part of the work was carried out by the implementation of HR-MAS technique with the experimental conditions optimisation and the technique evaluation in the study of Citrus leaves. The evaluation of the technique was carried out by the distinction among six Citrus sinensis varieties, as the indicator for the defence substances present in leaves of Citrus sinensis grafted in Citrus limonea and the detection and identification of the defence substances in leaves of Citrus spp under the plague attack.
Study and application of HS-MAS and DOSY NMR techniques in plants and plants extract from rutales order
Keywords: Química orgânica; Produtos naturais (química orgânica); Ressonância magnética nuclear; Difusão; DOSY; HS-MAS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA